Sarkasme Pada Meme di Media Sosial Instagram - Pratiwi, Veronika Unun (GERAM: Gerakan Aktif Menulis, 2022)
This study aims to determine the stylistic style of Sarcasm in Indonesian memes on Instagram. This study takes a formal object, namely stylistics, and a material object in the form of Indonesian memes on Instagram. The two objects were appointed as research material because they were motivated by meme problems and at least stylistic research in linguistics. The purpose of this study was to determine the analysis of memes through stylistic studies. The method used in this research is descriptive research in the form of qualitative. The data used is in the form of memes taken on Instagram with the condition that the meme uses language styles and language symptoms (majas). The results of this research data analysis are: (1) memes use language as a medium, including written language and images that are mutually supportive for the emotional formation of readers. (2) memes have language style and language symptoms. (3) memes use more than one figure of speech. With the existence of memes in the digital world, such as creating memes in this satirical review, the creative platform for reviews becomes open and diverse. Memes can be humorous as well as thought-provoking material about what's going on. So the meme became a new reaction to the events of the nation, especially in political and social life. Memes clarify attitudes of criticism and irony, but can also create irony and criticism in humour.